Perencanaan Kebijakan dan Strategi Pengelolaan Energi Indragiri Hilir Menggunakan Model Long Range Energy Alternative Planning System (LEAP) dalam Skenario Business as Usual (BAU) - Roberta Zulfhi Surya; M. Gasali (Universitas Bunda Mulia, 2017)
The energy was a key component for a local development and also was a sustainable strategy that impacts the community prosperity. The availability of energy was an important matter even it was a parameter for supporting local development success. Therefore, energy managing and planning must be taken seriously by the government in common things, this research aims to reform energy strategy and planning policy by using the Long Range Energy Alternative Planning System (LEAP) model on BAU scenario. The result of this research was an Indragiri Hilir’s energy need projection in 2025 also policy, strategy, and instrumental policy, effort, institution and energy development program that support energy managing policy.Keywords: Energy, Energy Plan, LEAP Model, BAU Skenario